Pelatihan Pemanfaatan Aplikasi Pemantauan Harga Barang Pokok dan Penting Bagi Petugas Pasar Se-Nusa Tenggara Barat - Adam Bachtiar Maulachela; Indriaturrahmi; Akbar Juliansyah; Iwan Desimal; Raden Fanny Printi Ardi (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2021)
The Trade Office of the West Nusa Tenggara (NTB) Provincial Government has developed an application for monitoring the prices of basic and important goods in all traditional markets in NTB. The main purpose of the application is so that information on the movement of prices for basic and important goods can be monitored more quickly and precisely. However, in its implementation, market officers who will use the application experience difficulties. Therefore, we need a program of debriefing for all market officers. The program is in the form of training and mentoring in order to improve the ability of market officers to use and access technology. This activity is carried out in three stages, namely preparation, implementation, and evaluation. The preparatory activities began with holding a Fourm Group Discussion (FGD), then compiling training materials, as well as video tutorials and application guide pocketbooks. Furthermore, the training is carried out online using Zoom Meeting. The location of the presenters at the training used the Mandalika University of Education (UNDIKMA) Mini Studio. Meanwhile, to facilitate mentoring activities, a WhatsApp Group was created. The result of this activity is the implementation of training on the use of applications to market officers. This activity has also produced a pocket book on the use of applications, and video tutorials. Based on the evaluation results, it is known that market officers are able to actively use and understand the functions and benefits of the application. This shows that this service activity has succeeded in increasing the skills of market officers in using price monitoring applications